THE IMPACT OF LOCAL POLITICAL DYNAMICS ON THE EXISTENCE AND SUSTAINABILITY OF BUMDES IN GALAGAMBA VILLAGE - Harmono, Harmono (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
This study seeks to investigate the impact of local political dynamics on the establishment and long-term viability of village-owned firms, focusing on a case study conducted in Galagamba Village, Ciwaringin District, Cirebon Regency, West Java. This study employs a qualitative methodology utilizing descriptive research techniques. The data was gathered through conducting comprehensive interviews, making observations, and analyzing relevant documents. The research findings indicate that the presence and longterm viability of village-owned firms in Galagamba Village, Ciwaringin District, Cirebon Regency, West Java are greatly affected by the local political dynamics. Political disagreements, power dynamics, and resource allocation can significantly impact the outcomes of village-owned enterprises. Political meddling can often incite conflicts between ethnic and ideological community groupings, impeding the progress of village business growth. In addition, alterations in local government policies, which are shaped by local political dynamics, can also detrimentally affect the survival and long-term viability of village-owned firms. This research suggests that it is crucial to include local political dynamics when creating and implementing business development plans at the village level. Both village communities and local governments must prioritize local political factors to ensure the continued presence and sustainability of successful village-owned firms.